Modelling and Simulation of Radar Based Target Detection and Speed Control for Automated Guided Vehicles - K. Manjunatha Chari, P. Parthasaradhy (International Journal of Advanced Science and Technology, 2019)
Highway impediment identification is a crucial and prolific work in dynamic hands on situations in an automated guided vehicular drive. As the upcoming technological innovations keep updating in the field of vehicular automations. It endows humans a complacence and act as a shield against collisions. The need of the hour in automotive vehicular propulsion is to implant a system that unveils alert signals on safety empowered with self-intelligence. In the proposed work, an anti-collision system is initiated. It identifies the existence of an impediment before it and at places unidentifiable on various counts of AVG and controls clash of the vehicles with dynamic (or) static impediments. The aforesaid puts in place on ultra-sonic based radar detector for identification of current situations be it be maneuver (or) static impediments, Coupled with the systemic core amalgamation of software and hardware object. Its embedded unit, where the hardware gets the obstacle information via ultrasonic based radar and software enumerates the distance of obstacles. Here in this work modeling and simulation of ultrasonic based radar is carried out for single and multiple targets at the front of AGV. To model mathematical derivations are applied and to simulate MATLAB is used. The results for both the type of targets are shown to prove this approach can be applied in AGV to operate on multi target roads. Keywords: -Automated Guided Vehicle, Radar, Ultrasonic sensor and Multi Target Detection.